PENGARUH ELECTRONIC WORD OF MOUTH, BRAND IMAGE, DAN LIVE STREAMING TERHADAP KEPUTUSAN PEMBELIAN PRODUK NPURE PADA MARKETPLACE SHOPEE - Sholikhah, Nia Inayatus; Marlena, Novi (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
In this digital era, one of the skincare products that follows the development by utilizing the shopee marketplace and its various features is Npure. The live streaming feature on the shopee marketplace is one of the triggers for the formation of electronic word of mouth (e-WOM) and forms a positive brand image in the minds of consumers, which in turn can influence consumers in making purchasing decisions for a product. This study aims to determine the effect of e-WOM, brand image, and live streaming on purchasing decisions for Npure products on the shopee marketplace. The type of research used is quantitative, sourced from primary data obtained from the results of a questionnaire via a google form link. The results showed that e-WOM has a positive effect on purchasing decisions for Npure products in the shopee marketplace, brand image has a positive effect on purchasing decisions for Npure products in the shopee marketplace, and live streaming has a positive effect on purchasing decisions for Npure products in the shopee marketplace. Simultaneously e-WOM, brand image, and live streaming have a positive effect on purchasing decisions for Npure products on the shopee marketplace. Keyword : Brand Image; Electronic Word of Mouth; Live Streaming; Purchasing Decisions